Challenges faced by Bangladesh in opening LC amid dollar crisis and policy recommendations for overcoming them - Kar, Srijoni (Brac University, 2024)
This research paper is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2023.